Vertebral Augmentation is Superior to Nonoperative Care at Reducing Lower Back Pain for Symptomatic Osteoporotic Compression Fractures: A Meta-Analysis. Issue 8 (October 2018) - Pourtaheri, Sina; Luo, William; Cui, Christina; Garfin, Steven
Abstract : Study Design: This is a systematic review and meta-analysis. Objective: This study's goal was to (i) assess the clinical outcomes with and without vertebral augmentation (VA) for osteoporotic vertebral compression fractures (VCFs) with versus without correlating signs and symptoms; and (ii) acute (symptoms <3 mo duration) and subacute VCFs (3–6 mo duration) versus chronic VCFs (>6 mo). Summary of Background Data: Previously, a randomized controlled trial in the New England Journal of Medicine concluded that vertebroplasty for osteoporotic VCFs provided no clinical benefit over sham surgery. However, the VCFs examined had no clinical correlation with symptom, physical examination, or imaging (magnetic resonance imaging/bone scan) findings. Nonetheless, the randomized controlled trial resulted in a reduction in VA performed in the United States. Currently, no consensus exists on VA versus nonoperative care for symptomatic VCFs (SVFs). Materials and Methods: A literature search was conducted for studies on VA and conservative management for VCFs. Meta-analysis was performed using the random-effects model. The primary outcome was improvement in lower back pain visual analog score. SVFs were defined as radiographic VCF with clinical correlation. Radiographic-alone VCF (RVF) was defined as radiographic VCF without clinical correlation. Results: Thirteen studies totaling 1467 patients with minimum 6-month follow-up were found. Pain reduction was greater with VA over conservative management for SVFs ( P <0.000001) and equivalent for RVFs ( P =0.22). Subanalysis for acute/subacute SVFs and chronic SVFs showed that VA was superior to nonoperative care ( P =0.0009 and 0.04, respectively). No difference was observed in outcomes between VA and nonoperative care for chronic RVF ( P =0.22). Conclusions: VA is superior to nonoperative care in reducing lower back pain for osteoporotic VCFs with correlating signs and symptoms. VA had no benefit over nonoperative care for chronic VCFs that lacked clinical correlation. Lower back pain has many etiologies and patients should be clinically assessed before recommending VA.